“Magkalambigit” (Intertwined) / Krizia Mae Villamil - Villamil, Krizia Mae (Faculty of Art and Design, 2021)
“Magkalambigit” (Intertwined) is my personal love letter for the endemic Negros Bleeding-Heart Pigeon of the Philippines. I have always been fascinated with the different species of animals that inhabit our planet along with their history, habitat, and life in general. So, I wanted to try to capture the essence of their existence through my art. The Negros Bleeding-Heart Pigeon are critically endangered species that can only be found in the Philippines. There are estimated around 50 - 400 Negros Bleeding-Heart Pigeons leftin the region of Negros and Panay and are continually declining due to deforestations. Known for their thin vivid red patch on their breast which resembles a punctured wound, this quality makes them different from other bleedingheart pigeons within the country which usually have a bigger red patch. Due to continous habitat degradation and charcoal burning within the forests of Negros, their species are continously declining and my intention is to give importance and spotlight to them by encapsulating them through my sculpture. It is very hard to find a Negros Bleeding-Heart Pigeon in today’s era so my sculpture is a sort of monumental reverence to this species. They are elusive and I pictured them as being elegant so I added these intricate pattern which resembles the patterns used in weaves of Negros Occidental region.